KEPEMIMPINAN, MOTIVASI, LINGKUNGAN KERJA DAN KINERJA KARYAWAN DI PT. NIRO CERAMIC INDONESIA - Rachmat Setyawan (JURNAL LENTERA BISNIS, 2017)
The purpose of the study or research is to know more about how leadership, motivation, and working environment influencing on employee performance and for finding which is as dominant factor from those variables. The research method used is multi linier regression to test leadership, motivation and working environment variable to employee performance. 375 employees were taken as sample from the employee population. The result of research showed that determination coefficient obtained is 0.476 (or equal to 47.6%), this means changing at employee performance simultaneously determined from variable of leadership, motivation and working environment by 47.6%, and the rest about 52.4% determined by other variables which are not focused in this research. Research also showed that there is a significant influent from leadership, motivation, and working environment variable to employee performance. Motivation variable becomes the dominan variable affecting the employee performance by 0.400, then working environment variable by 0.234 and the last leadership by 0.107. Key words: Leadership, Motivation, Environment, and Performance